2021
DOI: 10.3390/w13192731
|View full text |Cite
|
Sign up to set email alerts
|

Biofunctionalization of Cork with Moringa oleifera Seeds and Use of PMA Staining and qPCR to Detect Viability of Escherichia coli

Abstract: Cork matrices biofunctionalized with Moringa oleifera seed extracts (MoSe) have potential for use as a biofilter with antibacterial properties to reduce waterborne pathogens. The aim of this study was to evaluate the effect of cork biofunctionalized with active antimicrobial compounds of MoSe (f-cork) on the inhibition of Escherichia coli (InhEc). The LacZ gene from a strain of E. coli was used as the target sequence using viability quantification Polymerase Chain Reaction (qPCR) and differentiation of viable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
(65 reference statements)
1
3
0
Order By: Relevance
“…In a previous work, XPS and FTIR analyses revealed that the mild conditions used at the present work (i.e., low temperature and mild-alkaline pH) during AgLNP synthesis ensure a low extent of lignin oxidation, preserving the phenolic moieties required for the laccase-assisted NPs immobilization onto the cork [ 43 ]. All the results herein obtained for AgLNP characterization were in agreement with those previously reported in other works from our group [ 28 , 41 , 43 , 44 ].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In a previous work, XPS and FTIR analyses revealed that the mild conditions used at the present work (i.e., low temperature and mild-alkaline pH) during AgLNP synthesis ensure a low extent of lignin oxidation, preserving the phenolic moieties required for the laccase-assisted NPs immobilization onto the cork [ 43 ]. All the results herein obtained for AgLNP characterization were in agreement with those previously reported in other works from our group [ 28 , 41 , 43 , 44 ].…”
Section: Resultssupporting
confidence: 92%
“…Therefore, this method is a fast and eco-friendly approach to obtain nanocomposite materials with durable and efficient coatings. On the other hand, the enzymatic immobilization is a very complex process that involves different interactions/reactions between the cork surface and the AgLNP, such as electrostatic interactions, hydrogen bonds, and covalent bonds between laccase-activated cork residues and the AgLNP [ 44 ]. Cork chemical composition can vary according to its origin in the range of 40–60% suberin, 10–50% lignin, 5–15% polysaccharides, and 10–25% extractable components (e.g., waxes and tannins).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA intercalating dyes are able to enter dead cells without damaging their membrane integrity and intercalate with DNA using their photo-inducible azide groups, preventing PCR-induced DNA amplification [7,8]. Viable qPCR assays with PMA have been successfully optimized to detect major foodborne pathogens, including E. coli O157:H7, Salmonella spp., and Listeria monocytogenes [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%